Physiological and metabolome characterization of Amaranthus hybridus L. grown under cypermethrin stress: an insight of Jasmonic acid treatment - Arun Kumar; Pradeep Kumar Yadav; Anita Singh (BMC Plant Biology)
Abstract The indiscriminate use of pesticides compromises physiology and metabolism in crops, posing health risks through residue accumulation in edible tissues. Amaranthus hybridus L., a fast growing, nutritionally and medicinally valuable crop was studied here to assess the impact of cypermethrin (CYP) at recommended (R1, 100 ppm) and double dose (R2, 200 ppm) alongside foliar application of jasmonic acid (JA) at 50 µM, 100 µM, and 200 µM concentrations. CYP at R1 dose induced hormesis, while R2 was toxic, elevating the production of ROS molecules (H2O2, SOR, MDA). JA application upregulated the antioxidant activity of SOD, POD, APX, GST, DHAR, GSH, and proline to alleviate oxidative stress and improve growth indicators, including shoot length, leaf area, chlorophyll content, Fv/Fm ratio, and biomass. JA at 100 µM yielded the highest increase in biomass, 11.52% and 13.7% for R1 and R2 treated plants, respectively and also led to reduced accumulation of CYP residues. The UHPLC-MS analysis of leaf tissue revealed increase in the contents of carotenoids, flavonoids, phenolics, phenylpropanoids, steroids content in the plant group combinedly treated with JA and CYP compared to those treated with CYP alone, indicating a protective and growth-promoting role of JA under pesticide stress conditions. Overall, 100 µM concentration of JA proved to be effective against the stress induced by the either dose of CYP in the study. These insights could offer strategies to reduce pesticide-induced damage in vegetable crops, advancing sustainable agriculture.